Jacqueline O'Brien interviewed by Vernon O'Brien in the Australia 1938 oral history project - O'Brien, Jacqueline; O'Brien, V. T. (Vernon Thomas); Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
O'Brien speaks of her family background ; memories of the Depression ; school and childhood memories in Darwin ; secondary schooling in Sydney ; religion ; entertainment ; health and healthcare ; family life ; living conditions ; servants and Aboriginal help at that time ; description of hotel owned by parents ; memories of 1938 ; local Chinese ; social life and entertainment ; local Aborigines ; politics ; memories of 1937 cyclone ; family travel ; local people and customs.
Full transcript unavailable, interview summarised (6 p.)
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Timed summary available.
Keywords: O'Brien, Jacqueline -- Interviews; Aboriginal Australians -- Northern Territory -- Social conditions; Darwin (N.T.) -- Social conditions -- 1901-1945.; Darwin (N.T.) -- Social life and customs -- 1901-1945.